AIP1 suppresses neovascularization by inhibiting the NOX4-induced NLRP3/NLRP6 imbalance in a murine corneal alkali burn model - Qingyu Li; Xia Hua; Liangpin Li; Xueyan Zhou; Ye Tian; Yang Deng; Min Zhang; Xiaoyong Yuan; Wei Chi (Cell Communication and Signaling, 2022)
Abstract Background Apoptosis signal-regulating kinase 1-interacting protein 1 (AIP1) participates in inflammatory neovascularization induction. NADPH oxidase 4 (NOX4) produces reactive oxygen species (ROS), leading to an imbalance in nucleotide-binding oligomerization domain-like receptor family pyrin domain containing 3 (NLRP3) and NLR family pyrin domain containing 6 (NLRP6) expression. The mechanisms of AIP1, NOX4, ROS and inflammasomes in corneal neovascularization were studied herein. Methods C57BL/6 and AIP1-knockout mice were used in this study. The alkali burn procedure was performed on the right eye. Adenovirus encoding AIP1 plus green fluorescence protein (GFP) (Ad-AIP1-GFP) or GFP alone was injected into the right anterior chamber, GLX351322 was applied as a NOX4 inhibitor, and then corneal neovascularization was scored. The expression of related genes was measured by quantitative real-time polymerase chain reaction, western blotting and immunofluorescence staining. 2′,7′-Dichlorofluorescin diacetate staining was used to determine the ROS levels. Results The expression of AIP1 was decreased, while that of cleaved interleukin-1β (clv-IL-1β) and vascular endothelial growth factor A (VEGFa) was increased after alkali burn injury. NOX4 expression was increased, the imbalance in NLRP3/NLRP6 was exacerbated, and corneal neovascularization was increased significantly in AIP1-knockout mice compared with those in C57BL/6 mice after alkali burns. These effects were reversed by AIP1 overexpression. NLRP3/NLRP6 expression was imbalanced after alkali burns. GLX351322 reversed the imbalance in NLRP3/NLRP6 by reducing the ROS levels. This treatment also reduced the expression of clv-IL-1β and VEGFa, suppressing neovascularization. Conclusions AIP1 and NOX4 can regulate corneal inflammation and neovascularization after alkali burn injury. Based on the pathogenesis of corneal neovascularization, these findings are expected to provide new therapeutic strategies for patients. Plain English summary Corneal alkali burn injury is a common type of ocular injury that is difficult to treat in the clinic. The cornea is a clear and avascular tissue. Corneal neovascularization after alkali burn injury is a serious complication; it not only seriously affects the patient’s vision but also is the main reason for failed corneal transplantation. Corneal neovascularization affects approximately 1.4 million patients a year. We show for the first time that AIP1 and NOX4 can regulate corneal inflammation and neovascularization after alkali burns. The expression of AIP1 was decreased, while that of clv-IL-1β and VEGFa was increased after alkali burns. We tried to elucidate the specific molecular mechanisms by which AIP1 regulates corneal neovascularization. NOX4 activation was due to decreased AIP1 expression in murine corneas with alkali burns. NOX4 expression was increased, the imbalance in NLRP3/NLRP6 was exacerbated, and corneal neovascularization was increased significantly in AIP1-knockout mice compared with those in C57BL/6 mice after alkali burns. These effects were reversed by AIP1 overexpression. Additionally, NLRP3/NLRP6 expression was unbalanced, with NLRP3 activation and NLRP6 suppression in the corneal alkali burn murine model. Eye drops containing GLX351322, a NOX4 inhibitor, reversed the imbalance in NLRP3/NLRP6 by reducing ROS expression. This treatment also reduced the expression of clv-IL-1β and VEGFa, reducing neovascularization. Therefore, we provide new gene therapeutic strategies for patients. With the development of neovascularization therapy, we believe that in addition to corneal transplantation, new drug or gene therapies can achieve better results. Video Abstract